Bahasa Inggris - Ria Suci Permatasari; Dhany Efita Sari (Universitas KH. Abdul Chalim Mojokerto, 2025)
The culinary industry in Indonesia has seen significant growth, driven by evolving consumer preferences and innovations in food presentation. Bento cakes, originating from South Korea, have emerged as a popular product with high demand, resulting in a rapid expansion of bento cake home industries. Despite this promising market, the growing competition poses challenges for business owners, particularly in developing effective marketing strategies. This study investigates marketing strategies by adopting an order-based marketing strategy and examines the operational challenges faced by bento cake home businesses. Utilizing a qualitative approach and phenomenological methodology, data were collected through in-depth interviews, observations, and documentation with business owners and customers. Findings indicate that an order-based marketing strategy enhances customer satisfaction by offering personalized services and improves production efficiency and transaction convenience. However, operational constraints include human error and limited customer understanding of the ordering process, often leading to dissatisfaction. Furthermore, while social media marketing contributes positively to business reach and engagement, issues remain in effectively communicating order procedures and managing operations efficiently. The study highlights the need for continuous production and order management improvement to mitigate errors and enhance customer comprehension. Recommendations include regular training for staff to minimize errors, refining information dissemination strategies on social media, and enhancing operational processes to optimize customer experience. These findings underscore the importance of adapting marketing strategies to maintain competitiveness in Indonesia’s dynamic culinary landscape.